Valuing the role of living aquatic resources to rural livelihoods in multiple-use, seasonally-inundated wetlands in the Yellow River Basin of China, for improved governance - Kam, Suan Pheng (CGIAR Challenge Program on Water and Food, 2010)
Supported by the CPWF, this two-year project titled “Valuing the role of living aquatic resources to rural livelihoods in multiple-use, seasonally-inundated wetlands in the Yellow River Basin of China, for improved governance” focused on linking the use of wetlands resources by local communities and value of wetlands ecosystem services with management implications for the riverine and coastal wetlands in Henan and Shandong provinces. A study on this Chinese situation of pursuing a rapid development agenda while recognizing the need to conserve critical wetland areas would provide insights on the issues and possible avenues for sustainable wetlands management that may be relevant to other developing countries.